Defense industry policy strategy in developing the national defense system to strengthen national security - Suadnyana, I Nyoman; Aritonang, Sovian (Universitas Negeri Malang, 2025)
Indonesia’s defense policy is shaped by the growing complexity of military, non-military, and hybrid threats that challenge national sovereignty and territorial integrity. In response to these evolving threats and the broader VUCA (volatility, uncertainty, complexity, ambiguity) environment, Indonesia has implemented the Sishanta strategy, an integrated defense approach combining military and civilian resources. This study examines the strategic role of Indonesia’s defense industry in strengthening national security, with particular emphasis on the development of indigenous defense technologies (Alutsista) and the importance of public-private collaboration. Despite its strategic position in Southeast Asia and increasing modernization efforts, Indonesia continues to face critical obstacles, including reliance on foreign technology, limited skilled human capital, and weak innovation capacity. The research identifies key strategies to overcome these challenges, such as promoting technology transfer, increasing investment in research and development, and enhancing workforce capabilities. The findings underscore the need for a comprehensive and integrated policy framework to support defense self-reliance and ensure long-term national security in an increasingly unpredictable global landscape.